A brief mapping of identity politics: the anti-racist feminist and Afro-descendant women’s movement in Ladino Amefrica - Yuderkys Espinosa Miñoso; Ochy Curiel Pichardo (Tapuya)
In this article, we propose a mapping of the political identities of the anti-racist feminist and Afro-descendant women’s movement in Latin America and the Caribbean from the 1980s onwards. We do so as organic activists and intellectuals, witnesses of more than thirty years of feminist, lesbofeminist, Afro-descendant, and anti-racist movements in the region. The mapping starts with our first contacts and incursions into this movement and reaches the present day when we are more dedicated to critical theorizing, research, and teaching committed to anti-racist and decolonial struggles. In the spirit of a dictionary, we take up the different names with which Black women and Afro-descendants position and make themselves known, showing that many of these names respond to different genealogies and political stances that we are interested in characterizing, to account for the richness of the movement.